Perceptions of Micromanagement: Insights from the Saudi Labor Market - Aljabri, Bandar S.; Alharthy, Abdullah H. (Journal of Ecohumanism, 2025)
This study explored employees' perceptions of micromanagement in the Saudi labor market and its link to negative outcomes. Using a survey of 107 participants, it assessed the impact of micromanagement on stress, creativity, job satisfaction, productivity, and turnover intentions. Results showed a generally neutral view of micromanagement, with varying experiences across respondents. However, micromanagement contributed to increased stress, reduced job satisfaction, limited creativity, and higher turnover rates. The findings highlight the need for empowering and autonomy-supportive management practices. Age, gender, and sector did not significantly influence perceptions of micromanagement, though employees aged 30-40 reported the highest levels of supervisory intervention. Hypotheses 4-15 were confirmed, showing a weak but positive correlation between micromanagement and several negative outcomes, including stress, impaired creativity, decreased productivity, and increased turnover intentions. This emphasizes the importance of management styles that foster employee autonomy and well-being.